KARAKTERISASI JAMUR TIRAM PUTIH DENGAN MEDIA JAGUNG BULAT MENGGUNAKAN FOURIER TRANSFORM INFRARED - Irlian Nurmaniah; Fitrah Hadi Firdaus; Ana Fitriana; Maya Risanti; Irmansyah Irmansyah; Irzaman Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The production of white oyster mushroom with a variation of load time baglog after an incubation period has been investigated. Based on the results obtained FTIR molecular C-O, C=O, C-H, and O-H on oyster mushrooms. Molecules C-O, C=O, and C-H indicates carbohydrates and O-H molecules indicate the presence of water. The results obtained from the characterization of Fourier Transform Infrared showed the opening day 35th after incubation mass has a moisture content which is small compared with the opening day 40th day and the 45th day. These results indicated a high transmittance value on the FTIR graph results. Keywords: FTIR, O-H cluster, white oyster mushroom, transmittance